Analysis of alternative splicing of cassette exons at single-cell level using two fluorescent proteins - Gurskaya, Nadya G. (Oxford University Press, 2012)
Alternative splicing plays a major role in increasing proteome complexity and regulating gene expression. Here, we developed a new fluorescent protein-based approach to quantitatively analyze the alternative splicing of a target cassette exon (skipping or inclusion), which results in an open-reading frame shift. A fragment of a gene of interest is cloned between red and green fluorescent protein (RFP and GFP)-encoding sequences in such a way that translation of the normally spliced full-length transcript results in expression of both RFP and GFP. In contrast, alternative exon skipping results in the synthesis of RFP only. Green and red fluorescence intensities can be used to estimate the proportions of normal and alternative transcripts in each cell. The new method was successfully tested for human PIG3 (p53-inducible gene 3) cassette exon 4. Expected pattern of alternative splicing of PIG3 minigene was observed, including previously characterized effects of UV light irradiation and specific mutations. Interestingly, we observed a broad distribution of normal to alternative transcript ratio in individual cells with at least two distinct populations with ∼45% and >95% alternative transcript. We believe that this method is useful for fluorescence-based quantitative analysis of alternative splicing of target genes in a variety of biological models.